Las técnicas plásticas en la consecución de la pinza digital en niños y niñas del nivel inicial de 4 años de edad de la unidad educativa Ángel Polibio Chaves” de la Ciudad de Guaranda, provincia de Bolívar, año 2023 - Torres Jaramillo, Ana Belén (2024)
The objective of this research work is to continue supporting the development of the digital tweezers based on plastic techniques in children of the initial level 2, at present teachers maintain the crumpling and tearing as one of the main techniques for the development of the digital tweezers, that is why it was necessary to carry out and show the teachers more of these techniques such as modeling and dactyl-painting. The objective was to establish the plastic techniques as methodological strategies in the achievement of the digital pincer in children of the initial level of 4 years old of the Educational Unit "Angel Polibio Chaves" of the city of Guaranda, province of Bolivar, where these techniques were worked with great success in which the children had a good development. An observation sheet was made with the children, in which the skills and deficiencies they had were evidenced. A survey was made to the teachers in order to know their work methodology and in this way try to improve the teaching-learning process. The research approach was mixed, both qualitative and quantitative, the type of study was field, bibliographic, explanatory and descriptive, inductive-deductive, analytical-synthetic and action research methods were used, so that thanks to everything collected a good research work was obtained.